Anatase TiO2 nanocrystals anchored at inside of SBA-15 mesopores and their optical behavior - Araujo, M. M.; Silva, L. K. R.; Sczancoski, J. C. [UNESP]; Orlandi, M. O. [UNESP]; Longo, E. [UNESP]; Santos, A. G. D.; Sa, J. L. S.; Santos, R. S.; Luz, G. E.; Cavalcante, L. S. (Elsevier B.V., 2016)
In this paper, a new synthesis method was proposed to obtain anatase titanium oxide (TiO2) nanocrystals anchored into SBA-15 molecular sieve, as a matrix assigned by the in-situ anchoring (ISA) method. Pure SBA-15 and modified with TiO2 nanocrystals at different Si/Ti molar ratios (R = 75, 50, and 25) were structurally characterized by X-ray diffraction (XRD), Micro-Raman and Fourier Transform infrared (FTIR) spectroscopies. Specific surface area, pore volume and average pore diameter were estimated using both Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) methods, respectively. Morphological aspects of these samples were observed by means of field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). Optical properties were investigated by ultraviolet-visible (UV-vis) diffuse reflectance spectroscopy. XRD patterns, Micro-Raman and FT-IR spectra indicate the TiO2 nanocrystals crystallized in a tetragonal structure anchored into the SBA-15 mesopores. BET and BJH methods prove a large amount of TiO2 nanocrystals were anchored inside of SBA-15 mesopores due to increase in surface area and average pore size of SBA-15 matrix. FE-SEM and TEM images showed the pure SBA-15 has an elongated hexagon-shaped microstructure, and an average size of 7.34 nm for 2D hexagonal mesopores. Moreover, ISA method was able to avoid blocking of mesopores, in addition promotes a significant increasing the impregnation rate of anatase TiO2 nanocrystals in SBA-15 matrix. A growth mechanism was proposed in order to explain the stages involved in the formation of TiO2-SBA mesoporous. UV-vis spectra revealed a dependence of the optical band gap energy (E-gap) with the decreasing of Si/Ti molar ratios. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: SBA-15 mesopores; TiO2 nanocrystals; Infrared; Growth mechanism; Optical band gap